Clinical Efficacy Between Intravenous Paracetamol and Intravenous Fentanyl for Propofol Deep Sedation in Colonoscopy: A Randomized Controlled Trial - Thiparporn T; Supan W; Amornyotin S (Drug Design, Development and Therapy)
Thanitthi Thiparporn, Wilaiporn Supan, Somchai Amornyotin Department of Anesthesiology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Somchai Amornyotin, Department of Anesthesiology, Faculty of Medicine, Siriraj Hospital, Mahidol University, Bangkok, 10700, Thailand, Tel +66 2419 7990, Fax +66 2411 3256, Email somchai.amo@mahidol.ac.thIntroduction: Sedation practices for colonoscopy indeed vary widely around the globe. Due to a lack of data on intravenous paracetamol, we aimed to investigate the clinical efficacy of intravenous paracetamol compared to intravenous fentanyl under propofol deep sedation for colonoscopy.Methods: A total of 225 patients who underwent colonoscopy at Siriraj Hospital were randomly assigned to two groups. All patients underwent deep sedation with propofol and received intravenous (iv) paracetamol (group P, n = 113) or iv fentanyl (group F, n = 112). All patients received a premedication of 0.02– 0.03 mg/kg of midazolam intravenously. Fifteen to thirty minutes before the procedure, patients in group P were administered 1000 mg of iv paracetamol, while those in group F received 0.001 mg/kg of iv fentanyl. All patients were oxygenated with 100% O2 via a nasal cannula, and deep sedated with titrated intravenous propofol. The primary outcome measure was the success rate of colonoscopy. The colonoscope reaching the ileocecal valve was an important marker for a successful colonoscopy. Secondary outcome measures included endoscopist and patient satisfaction, patient tolerance, ease of the procedure, and sedation-related complications during and immediately after the procedure.Results: All colonoscopies were successfully completed. There were no significant differences in patient characteristics, duration of the procedure, endoscopist and patient satisfaction, patient tolerance, or ease of the procedure between the two groups. However, group F experienced significantly higher rates of upper airway obstruction and oxygen desaturation during the procedure compared to group P. No serious complications were observed in either group.Conclusion: Intravenous paracetamol with propofol deep sedation in adult patients is non-inferior to intravenous fentanyl for successful colonoscopy completion. Sedation-related complications were relatively lower in the propofol deep sedation with iv paracetamol group compared to the propofol deep sedation with iv fentanyl group.Registration: This trial was registered with the Thai Clinical Trial Registry (TCTR 20190321002).Keywords: colonoscopy, propofol, deep sedation, intravenous paracetamol, fentanyl